2012
DOI: 10.1109/jsac.2012.120707
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Vehicles in the Smart Grid: A Mean Field Game Analysis

Abstract: In this article, we investigate the competitive interaction between electrical vehicles or hybrid oilelectricity vehicles in a Cournot market consisting of electricity transactions to or from an underlying electricity distribution network. We provide a mean field game formulation for this competition, and introduce the set of fundamental differential equations ruling the behavior of the vehicles at the feedback Nash equilibrium, referred here to as the mean field equilibrium. This framework allows for a consis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
99
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 16 publications
0
99
0
2
Order By: Relevance
“…In other words, each appliance regulates automatically and in a decentralized fashion its power demand based on the mains frequency. A similar concept characterizes a recent literature on "load control" in power systems [12,14,26,28,37]. In particular, [12] surveys issues related to the redistribution of the load away from peak hours and the design of decentralized strategies to produce a predefined load trajectory (see also [14]).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In other words, each appliance regulates automatically and in a decentralized fashion its power demand based on the mains frequency. A similar concept characterizes a recent literature on "load control" in power systems [12,14,26,28,37]. In particular, [12] surveys issues related to the redistribution of the load away from peak hours and the design of decentralized strategies to produce a predefined load trajectory (see also [14]).…”
Section: Introductionmentioning
confidence: 86%
“…This paper applies mean field game theory to dynamic demand management in the same spirit as [14,37]. The latter is a recent and promising research area aiming at improving resilience in power networks [3,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have tested methods and operation models in advanced countries as well as comparing various models in order to suggest reasonable approaches to the development of vehicle charging facilities in their own countries [11]. Others have analyzed the relationship among stakeholders in electric vehicle charging facility construction and operation projects from the perspective of game theory, which showed that the level of support from the government as well as the charging prices may affect the provision of charging facilities [12][13][14]. In addition, the layout of charging facilities [15][16][17] and business operation models have been analyzed [7].…”
Section: Introductionmentioning
confidence: 99%
“…The goal was to obtain ancillary service to help regulate the power grid, as in many prior works [2], [11].…”
Section: Introductionmentioning
confidence: 99%